Distribution pattern of Crimean–Congo Hemorrhagic Fever in Asia and the Middle East - Aslam, Munazza; Abbas, Rao Zahid; Alsayeqh, Abdullah (Frontiers in Public Health, 2023)
Crimean Congo Hemorrhagic Fever (CCHF) is one of the most important vector-borne diseases of zoonotic potential that can be acquired following biting of Hyalomma species of ticks infected with the virus. It is a highly prevalent disease found in most countries in Asia and the Middle East. Contact with infected tissue, blood, patient, or livestock in acute viremic phase, infected tick bite, or removal of tick mechanically with bare hands are the risk factors of the disease. The disease is clinically described as progressive hemorrhages, fever, and pain in musculature. Biochemical tests reveal elevated level of creatinine phosphokinase, alanine transaminase, aspartate aminotransferase, and lactate dehydrogenase. Clotting time is prolonged in pro-thrombin test. Pathogenesis is mostly related to the disruption of epithelium during viral replication and indirectly by secreting cytotoxic molecules that cause endothelial activation and result in loss of function. Treatment is attributed to the symptomatic method in which supportive therapy is given by means of blood or plasma infusions. According to the most advanced studies CCHF can be treated by Ribavirin. Healthcare staff are more prone to infection. The hemorrhagic phase represents a high risk for accidental exposures. Ribavirin, an antiviral when given as a prophylactic treatment shows excellent results in preventing the disease. This review presents a comprehensive overview of the zoonotic prevalence and significant risk factors that are attributable to CCHF viral infection from a regional point of view. Furthermore, pathology associated with CCHF virus along with pathophysiology is discussed. The legislation and policies implementation regarding public outreach, research, and development aimed at infection prevention and control is required at a global level.